Development and evaluation of a decellularized membrane from human dermis. (11th June 2012) - Bondioli, Elena; Fini, Milena; Veronesi, Francesca; Giavaresi, Gianluca; Tschon, Matilde; Cenacchi, Giovanna; Cerasoli, Serenella; Giardino, Roberto; Melandri, Davide
Abstract Interest is increasing in biological scaffolds for tissue regeneration, such as extracellular matrix (ECM) membranes, developed through soft tissue decellularization. The present study describes the development of a chemicophysical decellularization method applied to allogenic human‐derived dermis (HDM). To evaluate the absence of viable cells and the maintenance of ECM structure, biological, histological and ultrastructural assessments were performed on the HDM membrane. Residual DNA content and glycosaminoglycan (GAG) and collagen contents were quantified. Growth factor (GF) release was directly measured on HDM extracts and indirectly measured by assessing cell proliferation after administering extract to cultures. Tensile tests were performed to measure the effect of the decellularization technique on the mechanical properties of tissue. Histocompatibility was investigated after subcutaneous implantation in rats. Residual DNA, GAG and collagen content measurements, vitality index, histology and electron microscopy showed the efficiency of the decellularization process and preservation of ECM matrix and bioactivity. In HDM extracts, among the tested GFs, transforming growth factor‐β1 showed the highest concentration. HDM extracts significantly increased the proliferation rate of L929 fibroblasts in comparison with controls (p < 0.005, p < 0.05 and p < 0.0005). Maximum load and stiffness of HDM were significantly higher than those of cellularized dermis (p < 0.0005, p < 0.005). Histological and histomorphometric analysis of explanted samples showed that the membrane was integrated with host tissues in the absence of inflammatory reactions. Our results show that the decellularization method allowed the development of a human allograft dermal matrix that might be useful for soft tissue regeneration. Copyright © 2012 John Wiley & Sons, Ltd.